Knowledge Sharing: Exploring Institutional Policy and Educator Practice Through Eportfolios In Music And Writing - Blom, D.; Rowley, J.; Bennett, Dawn; Hitchcock, M.; Dunbar-Hall, P. (Academic Conferences Ltd., 2014)
Many higher education institutions have embraced e-Learning and urge, or make compulsory, engagement by academics. Despite this, it is often the educators themselves who take the initiative to engage with innovative e-learning approaches. These approaches, in turn, can influence both peer- and institution-wide thinking about e-Learning. This paper focuses on the introduction or extension of ePortfolios within the creative arts at four Australian universities. Each educator adopted the ePortfolio for a different purpose, and in doing so has influenced, or is at least being monitored by, their university. All four studies have resulted in the growth, development and enrichment of teaching and learning because of the ePortfolio's facility to engage students in such activities as reflection, ongoing student-teacher dialogue, collaborative essay writing, peer evaluation, identity formation, and the documentation of skills, competencies and graduate attributes for career awareness and employability. In sharing this knowledge the studies have also influenced curriculum design and e-learning policy. The academic literature notes institutional interest in ePortfolios in relation to career preparation, demonstrating and assessing student learning, academic advising, and addressing public accountability concerns by facilitating internal and external departmental review and accreditation. Within this paper we discuss the bi-directional impact and sharing of knowledge about ePortfolio use as it occurs between institution and educator. The study findings inform future development of curriculum, policy and practice for creative arts students and academics in a variety of higher education settings. Further, the findings suggest that ePortfolios provide an efficient and transparent means to archive and access student work, and that they facilitate internal and external departmental review and broader institutional assessment. © ACPIL